Research Work as a Means of the Future Primary School Teachers Training to Research Activity - Shkvyr, Oksana (Pedagogical Discourse, 2016)
In the article the attention is focused on the problem of training of the future primary school teachers to conducting pedagogical researches. It is noted that the question of organization of scientific-research work of the future primary school teachers in higher educational institutions under the new conditions requires more profound research. The tasks of organization of scientific-research work in higher pedagogical educational institutions have been cleared out. The main ways of scientific-research work of students is determined scientific-research work which is an integral part of the educational process and which is compulsory for all students, and scientific-research work of students outside the educational process, that is their participation in scientific circles. The essence, advantages and forms of educational-research work have been revealed. It was found that the complexity of the content and methods of research work of students depends on the training phase. Pedagogical tasks of the research character, which can be used at different stages of teaching students, have been offered. The course and diploma projects are determined the main types of educational-research work. The attention is focused on the specifics of the structure, content and execution of the course and diploma projects at various levels of higher education. It is found out that both students and their supervisors should take into account the common and significant differences in writing these types of research works. The importance and the content of the methodological manual «Support-Instructive Materials for Writing the Course and Diploma Projects», prepared by us in co-authorship with H. Dudchak, have been revealed. By the specific examples the implementation of the integrated approach to writing different kinds of scientific works has been shown. It is stated that the methodical recommendations in the manual are presented in the form of schemes, tables, theses, which greatly quickens and facilitates the process of individual work of a student as for the learning requirements for writing the course or diploma project. The conclusion about the importance of implementing the principles of professional orientation, continuity, gradual increase of the degree of independence in the organization of educational-research work of the future primary school teachers has been made. Key words: scientific-research activity; educational-research activity; course project; diploma project.